Konsep dan Urgensi Kodifikasi Hukum Indonesia - Berliana, Vicke; Adha, Adnan; Amin, Fadli; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Legal codification is the prosses of compling various legal provisions into a systematic, structured, and easily undestanable written document. In the Indonesia context, codification is essential due to the existing plurality of legal system, including customary law, criminal law, civil law, and modern statutory regulations. The plurality often results in regulatory overlap and legal uncertainty. This study aims to explain the concept of codification and its urgency for national legal reform. The research employs a qualitative descriptive approach through literature analysis. The findings indicate that codification serves not only to simplify regulations nut also to strengthen legal certainty, harmonize laws, and integrate the national legal system. Codification is viewed as a strategic step toward creating an effective, responsive, and socially relevant Indonesia legal system.